If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 + -3x = 1 Reorder the terms: 7 + 2x + -3x = 1 Combine like terms: 2x + -3x = -1x 7 + -1x = 1 Solving 7 + -1x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 1 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 1 + -7 -1x = 1 + -7 Combine like terms: 1 + -7 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| y=-0.02x+x+0.5 | | 3x+27=10x-33 | | -40=33x+15 | | 3=-x+1 | | 6(2x+1)-3(5x+2)=0 | | 8=8n-22-7n | | -x+3= | | y=-0.02x+x+6 | | 7=3(x-7)+10 | | 8x=16(x-36) | | x=-5+4 | | 3x+15=6x+7 | | 3(2-a)=8-a | | 3x-8=5(2x-3) | | 147-4x=23x+21 | | 5x=(6x-3) | | 5(2x-3)+6=43-3x | | 8+12x=15x-19 | | 2c+5=3c+7 | | 67-5x=9x+7 | | 3a-11=4 | | 60-x=2(x-36) | | 2x+6=-3 | | 104-x=2(x-29) | | 20x-9x-20=0 | | 3x+139=12x-14 | | x-9x-20=0 | | 4x-2=11x-43 | | 49-6x=12x+15 | | 5m(2m-7)=-5 | | -8x-y=-8 | | x^3-8x^2+15x+12=0 |